Multiple Sclerosis and SARS-CoV-2: Has the Interplay Started? - Bellucci, Gianmarco; Rinaldi, Virginia; Buscarinu, Maria Chiara; Reniè, Roberta; Bigi, Rachele; Pellicciari, Giulia; Morena, Emanuele; Romano, Carmela; Marrone, Antonio; Mechelli, Rosella; Salvetti, Marco; Ristori, Giovanni (Frontiers in Immunology, 2021)
Current knowledge on Multiple Sclerosis (MS) etiopathogenesis encompasses complex interactions between the host’s genetic background and several environmental factors that result in dysimmunity against the central nervous system. An old-aged association exists between MS and viral infections, capable of triggering and sustaining neuroinflammation through direct and indirect mechanisms. The novel Coronavirus, SARS-CoV-2, has a remarkable, and still not fully understood, impact on the immune system: the occurrence and severity of both acute COVID-19 and post-infectious chronic illness (long COVID-19) largely depends on the host’s response to the infection, that echoes several aspects of MS pathobiology. Furthermore, other MS-associated viruses, such as the Epstein-Barr Virus (EBV) and Human Endogenous Retroviruses (HERVs), may enhance a mechanistic interplay with the novel Coronavirus, with the potential to interfere in MS natural history. Studies on COVID-19 in people with MS have helped clinicians in adjusting therapeutic strategies during the pandemic; similar efforts are being made for SARS-CoV-2 vaccination campaigns. In this Review, we look over eighteen months of SARS-CoV-2 pandemic from the perspective of MS: we dissect neuroinflammatory and demyelinating mechanisms associated with COVID-19, summarize pathophysiological crossroads between MS and SARS-CoV-2 infection and discuss present evidence on COVID-19 and its vaccination in people with MS.